2022
DOI: 10.1002/jwmg.22331
|View full text |Cite
|
Sign up to set email alerts
|

Phenology‐specific space use by Rio Grande wild turkeys

Abstract: Conservation of wildlife populations necessitates identifying patterns in space use because fitness requirements influence resource selection; however, details on how phenology affects space use are often only cursorily addressed during development of space-and resource-use estimates. Moreover, spaceuse assessments often aggregate distinct, phenology-specific behaviors into generalized realizations of biological processes, such as reproduction. Therefore, to improve the relevance and accuracy of biological inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…We confirmed a hen was nesting once the hen began incubating a nest. A GPS‐transmitted hen was deemed as incubating a nest when GPS locations formed a ~25‐m diameter cluster, and the cluster contained one roost location at the presumed nest site (Moscicki et al., 2023 ; Yeldell et al., 2017 ). Hens with VHF transmitters were deemed incubating when they had decreased movements and then were inactive based on the activity switch during one triangulation (Johnson et al., 2022 ; Miller et al., 1998 ; Thogmartin & Johnson, 1999 ; Vangilder et al., 1987 ).…”
Section: Methodsmentioning
confidence: 99%
“…We confirmed a hen was nesting once the hen began incubating a nest. A GPS‐transmitted hen was deemed as incubating a nest when GPS locations formed a ~25‐m diameter cluster, and the cluster contained one roost location at the presumed nest site (Moscicki et al., 2023 ; Yeldell et al., 2017 ). Hens with VHF transmitters were deemed incubating when they had decreased movements and then were inactive based on the activity switch during one triangulation (Johnson et al., 2022 ; Miller et al., 1998 ; Thogmartin & Johnson, 1999 ; Vangilder et al., 1987 ).…”
Section: Methodsmentioning
confidence: 99%
“…We removed incubation locations from analyses because female wild turkeys remained on the ground at the nest location during this period. From the information described above, we were able to categorize reproductive phases for each female throughout the reproductive season, which we later used as a covariate in models to describe the temporal aspect of female roost selection ([ 64 ]; table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…including all covariates), a resource model, a feature model and a null model (table 3). Each model included an interaction of the reproductive phase for each female [64]. We used a generalized linear mixed model with a binomial response distribution (logistic regression) and logit link to the used-available data [81,83].…”
Section: Resource Selection Modelmentioning
confidence: 99%
“…Contemporary research has shown that prior to laying, female wild turkeys do not prospect for potential nest sites [ 17 ], but it is plausible that individuals may prospect for resources during the laying period [ 16 ]. Furthermore, pre-nesting and laying ranges show little overlap [ 71 ], and during laying, females increase daily movements but decrease space use, indicative of a lack of site familiarity [ 31 , 48 , 71 ]. It is plausible that movement behaviors during the laying period may maximize foraging success and reduce predation risk during the incubation period [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%